Timed artificial insemination in yearling beef heifers: 7-11 Cosynch VS. Cosynch - Thompson, A.W.; Holladay, C.D.; Eborn, D.R.; Grieger, David M. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Previous research demonstrated that an estrus-synchronization program using a short period of melengestrol acetate (MGA) feeding in conjunction with a Cosynch protocol was effective in synchronizing estrus in postpartum beef cows. The objective of our study was to test this synchronization protocol (7-11 Cosynch) in yearling beef heifers in comparison to a Cosynch protocol. Fifty-eight commercial beef replacement heifers were assigned randomly to two protocols: Cosynch (n=29) and 7-11 Cosynch (n=29). Beginning on day 1, heifers in the 7-11 Cosynch protocol were fed MGA (0.5 mg/heifer daily) for 7 days. On day 7, the last day of MGA feeding, the heifers on the 7-11 Cosynch protocol received an injection of PGF2α. On day 11 all 58 heifers received an injection of GnRH (100 μg). On day 18, all 58 heifers were injected with PGF2α. On day 20, all of the heifers received a 100 μg dose of GnRH by injection and were artificially inseminated. Ultrasonography was used to determine pregnancy status 29 days after breeding. A greater percentage (P<0.01) of heifers were pregnant after the 7-11 Cosynch treatment (67%) than after the Cosynch treatment (31%). This study demonstrates the potential of achieving acceptable pregnancy rates using timed artificial insemination in yearling beef heifers.
Keywords: Beef; Timed Timed artificial insemination; 7-11 Cosynch VS. Cosynch; Yearling heifers